Human-wildlife ecological interactions shape Escherichia coli population and resistome in two sloth species from Costa Rica - Cristina Calvo-Fernandez; Marta M. Dolcet-Negre; Barbara Martin-Maldonado; Mario Pulido-Vadillo; Natalia Montero; Roger Such; Encarnación García-Vila; Jose F. Delgado-Blas; Bruno Gonzalez-Zorn (npj Antimicrobials and Resistance)
Abstract Antimicrobial resistance (AMR) is a global health concern, with natural ecosystems acting as reservoirs for resistant bacteria. We assessed AMR in Escherichia coli isolated from two wild sloth species in Costa Rica. E. coli from two-toed sloths (Choloepus hoffmanni), a species with greater mobility and a broader diet, showed resistance to sulfamethoxazole (25%), tetracycline (9.4%), chloramphenicol (6.3%), ampicillin (6.3%), trimethoprim (3.1%), and ciprofloxacin (3.1%), which correlated with the presence of resistance genes (tet(A), tet(B), bla TEM-1B , aph(3”)-Id, aph(6)-Id, sul2, qnrS1, floR and dfrA8). E. coli from three-toed sloths (Bradypus variegatus) showed 40% resistance to sulfamethoxazole despite no detected resistance genes, suggesting a regional effect. A significant negative correlation was found between AMR and distance to human-populated areas, highlighting anthropogenic impact on AMR spread. Notably, E. coli isolates from remote areas with no human impact indicate that some ecosystems remain unaffected. Preserving these areas is essential to protect environmental and public health.